Partial loss of CFIm25 causes learning deficits and aberrant neuronal alternative polyadenylation - Alcott, Callison E; Yalamanchili, Hari Krishna; Ji, Ping; van der Heijden, Meike E; Saltzman, Alexander; Elrod, Nathan; Lin, Ai; Leng, Mei; Bhatt, Bhoomi; Hao, Shuang; Wang, Qi; Saliba, Afaf; et al. (eLife, 2020)
We previously showed that NUDT21-spanning copy-number variations (CNVs) are associated with intellectual disability (Gennarino et al., 2015). However, the patients’ CNVs also included other genes. To determine if reduced NUDT21 function alone can cause disease, we generated Nudt21+/- mice to mimic NUDT21-deletion patients. We found that although these mice have 50% reduced Nudt21 mRNA, they only have 30% less of its cognate protein, CFIm25. Despite this partial protein-level compensation, the Nudt21+/- mice have learning deficits, cortical hyperexcitability, and misregulated alternative polyadenylation (APA) in their hippocampi. Further, to determine the mediators driving neural dysfunction in humans, we partially inhibited NUDT21 in human stem cell-derived neurons to reduce CFIm25 by 30%. This induced APA and protein level misregulation in hundreds of genes, a number of which cause intellectual disability when mutated. Altogether, these results show that disruption of NUDT21-regulated APA events in the brain can cause intellectual disability.
Keywords: learning deficits; NUDT21; CFIm25; alternative polyadenylation; gene regulation; intellectual disability